MULTIPLIKASI TUNAS DENGAN METODE KULTUR JARINGAN JERUK KUOK (Citrus nobilis Lour) MENGGUNAKAN HORMON BENZYL AMINO PURINE (BAP) DAN KINETIN SEBAGAI RANCANGAN LEMBAR KERJA SISWA BIOLOGI DI SMA - Safitri, Widia; Mahadi, Imam; ', Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted to determine the shoot multiplication by tissue culture methods Kuok orange (citrus nobilis Lour) using hormone benzyl amino purine (BAP) and kinetin as a draft worksheet in high school biology students. which was conducted in April-June 2016. The results used as the design Student Worksheet (LKS) teaching modern biology biotechnology concepts in class XII High School. The study consisted of two phases, the first phase of the shoot multiplication by tissue culture methods Kuok orange (citrus nobilis Lour) using hormone benzyl amino purine (BAP) and kinetin, using the experimental method completely randomized design (CRD) factorial 16 x 3. It consists of 16 treatments and 3 replications thus obtained 48 experimental design. The first factor was BAP with a level of treatment that is 0 ppm, 0.5 ppm, 1 ppm, 2 ppm, 3 ppm. The second factor is the level of treatment Kinetin with 0 ppm, 1 ppm, 3 ppm. Parameters measured were growing percentage of explants, shoots appear aged, high number of shoots and buds. Ananlisis amount of data tested by ANOVA and a further test DMRT at 5% level. The results showed when the percentage is growing explants treated with B0,5K3, B0,5K5, B1K5, B2K0, B2K1, B2K3, B2K5 (100%), the age of the fastest emerging shoots are B2K0 ie 5 HST, the highest number of shoot (7.1) and the treatment B2K5 the highest bud on B2K5 treatment with a mean shoot height (8.2 cm). The second phase, the design student worksheets using the model of Discovery Learning (Analysis and Design). Facts on this research can be designed to be a learning resource in the form of Student Worksheet (LKS) in tissue culture material concept of modern biotechnology in high school.Key words : BAP, Kinetin, Orange Kuok, Multiplication, Learning Resources